Dinamika Kepribadian Menurut Teori Sigmund Freud: Analisis Psikologi Sastra pada Tokoh Restu dalam Novel 'Secret Obsession' karya Anggarani - Alvian Rahmad IlhamPermadi; Pradipa Juan Reswara; Eva Dwi Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The aim of this research is that the researcher wants to know intimately about the personality structure of the Id, Ego, Superego of the character Restu in the novel entitled "Secreet Obsession" by Anggarani using qualitative research methods. The problem formulation of this research is, What is the personality structure of the character? Blessings to the novel entitled "Secreet Obsession" by Anggarani. In this research, the researcher used a qualitative descriptive method as a data collection method with the technique of reading and then recording important information related to the research. This research used a literary psychology approach with a theoretical basis of psychoanalysis from Sigmund Freud. The results of this research show that the Id personality structure has positive results. Dominant compared to other personality structures, the Id structure of Restu's character is shown through his ambition to take revenge on the perpetrator of his mother's murder and there are also several impulsive behaviors that arise from impulses that arise from Restu's Id personality structure. However, the Superego structure still contained within Restu, Restu's superego was shown when there was an allegation that Restu was the real perpetrator of the murder case of his mother, from this incident his moral values emerged in the form of his thinking that he could not possibly carry out such a reckless action as killing his mother.